Efforts to Improve Students' Critical Thinking Skills in Mathematics Learning by Implementing the Discovery Learning Model in Elementary Schools - Doni Apriliandi (Journal of Indonesian Primary School, 2025)
This study aims to examine the effectiveness of the Discovery Learning model in improving elementary students’ critical thinking skills in mathematics learning. The ability to think critically is an essential cognitive competency for understanding mathematical concepts, evaluating reasoning, and solving non-routine problems; however, many elementary students still demonstrate low analytical and reflective abilities. This research employed a quasi-experimental design involving two intact classes: an experimental group that received mathematics instruction using Discovery Learning and a control group that was taught through conventional direct instruction. Data were collected through a validated critical thinking test consisting of indicators such as identifying problems, analyzing information, evaluating arguments, and constructing solutions. The results revealed that students in the experimental group achieved significantly higher posttest scores, with a mean gain of 0.67 compared to 0.34 in the control group. Students taught through Discovery Learning also demonstrated greater fluency in providing justifications and articulating reasoning processes. These findings indicate that Discovery Learning promotes deeper cognitive engagement, encourages inquiry-based reflection, and strengthens students’ ability to construct and evaluate mathematical ideas. The study has practical implications for elementary mathematics instruction, emphasizing the need for learner-centered pedagogical approaches that foster critical thinking from an early age.